Factors of digital accessibility and infrastructure on critical thinking skills of elementary school students in Bululawang village, Blitar - Aryasatya Rafa Prayitno; Angelina Sekar Larasati; Azka Putri Akbar; Achmad Dally Noer; Fildzah Arifah Kania; Inggit Rahma Safitri; Leli Farida; Ma’ruf Rodzi’in; Maria Avellia Karisya Windiyana; Rifqi Sani Pradana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
School participation across regions in Indonesia reflects significant disparities in access to and quality of education. This study aims to analyze the relationship between digital accessibility and infrastructure on the critical thinking abilities of elementary school students in Bululawang Village, Blitar Regency. Despite being one of the smallest villages with a low population, it still reflects a substantial educational gap between elementary schools within the same locality. This research employs a comparative method with a quantitative-qualitative approach, collecting data through interviews, observations, documentation studies, and focus group discussions (FGD). The U Mann-Whitney test analysis results indicate a significant difference in the distribution of critical thinking abilities, with UPT SD N Bululawang 01 performing significantly better than UPT SD N Bululawang 02. Better infrastructure, such as adequate roads and facilities, contributes to superior outcomes compared to other schools that still rely on unpaved roads and limited facilities. Interview findings also indicate an accessibility gap affecting teachers and students, reinforcing the importance of equitable educational infrastructure. This research aligns with efforts to improve the quality of education in Indonesia, particularly in reducing technology-based educational disparities in rural areas.